Best Value Investing Strategy: Analysis of Graham, Greenblatt, and Piotroski Methods for Smart Investment Decisions - Sihombing, Pardomuan; Putra, Wahyu Sastra (Research of Finance and Banking, 2024)
This study aims to analyze the value investment portfolio strategy based on prominent investors Benjamin Graham, Joel Greenblatt and Joseph Piotroski. The three portfolio models are built according to the methodology developed by each author, using the last five years of financial accounting data and through stocks listed on the Kompas 100 Index listed on the Indonesia Stock Exchange for the 2022 period. This study uses a three-factor model from the Fama and French method which is an extension of the Capital Asset Pricing Model methodology by adding Small Minus Big and High Minus Low. The regression results show that all three strategies produce positive and statistically significant coefficients in the three-factor model setting. After backtesting the three portfolios, Graham's portfolio has a higher return compared to the other two portfolios. The managerial implications of this study include the implementation of strategies based on strengthening financial fundamentals and operational efficiency to increase the company's attractiveness in the eyes of value-investing investors.